2019
DOI: 10.1111/ans.14990
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of defunctioning stoma following rectal cancer surgery: are we getting better? A population‐based single centre experience

Abstract: Background: The aim was to assess factors influencing the timing of defunctioning stoma (DS) reversal following low anterior resection of rectum for cancer (LAR). Methods: All patients operated with LAR and a primary DS during a 9-year period were included. Reversal later than 120 days after LAR was considered as delayed. A DS not reversed within 2 years was considered as permanent.Results: In the present study, median age at LAR was 67 years, 45% were females, median body mass index was 25, 87% had American S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
8
1
3
Order By: Relevance
“…DS reversal was impossible in 8 patients (5.2%) in this study. Gadan reported a reversal impossibility rate of 18% (20/110 cases) (21). The DS reversal rate in our study was higher than that reported in their study; however, DS reversal was achieved within 6 months after surgery in 55 patients (35.9%) and ≥2 years after surgery in many patients.…”
Section: Discussioncontrasting
confidence: 71%
“…DS reversal was impossible in 8 patients (5.2%) in this study. Gadan reported a reversal impossibility rate of 18% (20/110 cases) (21). The DS reversal rate in our study was higher than that reported in their study; however, DS reversal was achieved within 6 months after surgery in 55 patients (35.9%) and ≥2 years after surgery in many patients.…”
Section: Discussioncontrasting
confidence: 71%
“…Hence, early stoma reversal can help patients avoid the peristomal skin complications that have a significantly impact on quality of life and avoid long‐term consequences such as incisional hernia and chronic kidney disease. In a small subset of patients, as a result either of anastomotic complications from the index operation, progression of disease or due to multiple co‐morbidities, an ileostomy initially intended to be temporary may prove to be permanent 2,4 …”
Section: Discussionmentioning
confidence: 99%
“…Even a temporary loop ileostomy can detract significantly from a patient's quality of life 2 . Complications from a loop ileostomy such as skin irritation, retraction, prolapse, dehydration and electrolyte disturbance from high stoma output frequently lead to readmissions 2–4 . As many as 85–90% of patients undergoing loop ileostomy construction would not have experienced an anastomotic leak and need not have required their stoma but are still subject to its potential complications 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Proximal defunctioning stomas are commonly used to protect against the consequences of a leak 7,8 . Nevertheless, around 20 per cent of defunctioning stomas are never closed or are converted to an end colostomy 1,[9][10][11] , possibly contributing to higher than desired permanent stoma rates.…”
Section: Introductionmentioning
confidence: 99%